PKM2: A Potential Regulator of Rheumatoid Arthritis via Glycolytic and Non-Glycolytic Pathways - Xu, Danyi; Liang, Junyu; Lin, Jin; Yu, Chaohui (Frontiers in Immunology, 2019)
Immunometabolism provides a new perspective on the pathogenesis of rheumatoid arthritis (RA). In recent years, there have been investigations focusing on the role of intracellular glucose metabolism in the pathogenesis of RA. Previous studies have shown that glycolysis of synovial tissue is increased in RA patients, while glycolysis inhibitors can significantly inhibit synovitis. Pyruvate kinase (PK) is a key enzyme in glycolysis, catalyzing the final rate-limiting step in the process. An isoform of PK, PKM2, provides favorable conditions for the survival of tumor cells via its glycolytic or non-glycolytic functions and has become a potential therapeutic target in tumors. RA synovium has the characteristic of tumor-like growth, and, moreover, increased expression of PKM2 was identified in the synovial tissue of RA patients in recent studies, indicating the underlying role of PKM2 in RA. PKM2 has potential value as a new therapeutic target or biomarker for RA, but its exact role in RA remains unclear. In this review, the properties of PKM2 and existing research concerning PKM2 and RA are thoroughly reviewed and summarized, and the possible role and mechanism of PKM2 in RA are discussed.